KLAUSULA BAKU PERJANJIAN KREDIT PADA AKTA NOTARIS UNTUK MELINDUNGI KEPENTINGAN BANK - Muhammad Argian Azhar (Fakultas Hukum Universitas Sebelas Maret, 2023)
AbstractThe objective of this articles is to reveal and examine issues regarding the form of standard credit agreement on a notarial deed to protect the interests of the bank and legal protection granted to the bank through a standard clause on the credit agreement on the notarial deed. This articles includes normative legal research. The characteristics of this articles are the Perspective. The legal material collection technique is used to obtain the necessary legal materials so that by using documentation or document study techniques that are gathering material relevant to the problems and interviewing to the notary and the bank. While the analytical technique takes the deductive method. The results of the research concluded that notarial bank credit agreement deed will be very useful for creditors about the strength of the evidence, particularly by including the forms of standard clauses that are considered important in credit agreements, for instance, clauses regarding actions prohibited by banks that are prohibited primarily aimed at protecting the interests of banks both legally and economically, including the prohibition of requesting credit from other parties without the bank's permission or the prohibition to change the form of a company or the liquidation of a company without the bank's permission. Then with the clause on fines that are intended to reinforce the rights of banks to do both the size and condition, however in practice in banking making credit agreements with a deed under the counter can also provide guarantees of execution, because both the notary deed and under the counter always followed by other collateral institutions that the deed is executor. Besides, in the case of a non-performance of contract dispute between the debtor and the creditor, the deeds are not the base of reason used by. The Parties only have the problems with the non-performance of contract and not the deeds.Keywords: Notarial Deed; Interest of Bank; Standard Clause; Credit Agreement. AbstrakArtikel ini bertujuan untuk mengetahui dan mengkaji permasalahan mengenai bentuk klausula baku perjanjian kredit pada akta notaris untuk melindungi kepentingan bank dan perlindungan hukum yang diberikan kepada bank melalui klausula baku pada perjanjian kredit di akta notaris. Artikel ini termasuk penelitian hukum normatif. Sifat dari artikel ini adalah prespektif. Teknik pengumpulan bahan hukum menggunakan teknik dokumentasi atau studi dokumen dan wawancara dengan notaris serta pihak bank. Sedangkan teknik analisis dengan metode deduktif. Akta perjanjian kredit perbankan yang dibuat secara notariil akan sangat bermanfaat bagi kreditor tentang kekuatan pembuktiannya, terutama dengan mencantumkan bentuk-bentuk klausa baku yang di anggap penting dalam perjanjian kredit, seperti klausula mengenai tindakan yang di larang oleh bank yang pada utamanya bertujuan untuk melindungi kepentingan bank baik secara yuridis maupun secara ekonomis, diantaranya larangan untuk meminta kredit dari pihak lain tanpa seizin bank atau larangan mengubah bentuk perusahaan atau membubarkan perusahaan tanpa seizin bank. Kemudian dengan adanya klausula mengenai denda yang dimaksudkan untuk mempertegas hak-hak bank untuk melakukan pemungutan, baik mengenai besarnya maupun kondisinya. Namun dalam praktek di perbankan pembuatan perjanjian kredit dengan akta dibawah tangan juga dapat memberikan jaminan eksekusi, karena baik terhadap akta notariil maupun di bawah tangan selalu diikuti dengan lembaga jaminan lain yang aktanya bersifat eksekutorial. Disamping itu dalam sengketa wanprestasi antara debitor dan kreditor, akta-akta tersebut tidak menjadi alasan yang digunakan. Para pihak hanya mempermasalahkan wanprestasinya dan bukan aktanya.Kata Kunci: Akta Notaris; Kepentingan Bank; Klausula baku; Perjanjian Kredit.